Metabolic-Associated Fatty Liver Disease Is Highly Prevalent in the Postacute COVID Syndrome. (10th January 2022) - Milic, Jovana; Barbieri, Sara; Gozzi, Licia; Brigo, Alberto; Beghé, Bianca; Verduri, Alessia; Bacca, Erica; Iadisernia, Vittorio; Cuomo, Gianluca; Dolci, Giovanni; Yaacoub, Dina; Aprile, Emanuele; et al.
Abstract: Background: A proposal has recently been advanced to change the traditional definition of nonalcoholic fatty liver disease to metabolic-associated fatty liver disease (MAFLD), to reflect the cluster of metabolic abnormalities that may be more closely associated with cardiovascular risk. Long coronavirus disease 2019 (COVID-19) is a smoldering inflammatory condition, characterized by several symptom clusters. This study aims to determine the prevalence of MAFLD in patients with postacute COVID syndrome (PACS) and its association with other PACS-cluster phenotypes. Methods: We included 235 patients observed at a single university outpatient clinic. The diagnosis of PACS was based on ≥1 cluster of symptoms: respiratory, neurocognitive, musculoskeletal, psychological, sensory, and dermatological. The outcome was prevalence of MAFLD detected by transient elastography during the first postdischarge follow-up outpatient visit. The prevalence of MAFLD at the time of hospital admission was calculated retrospectively using the hepatic steatosis index. Results: Of 235 patients, 162 (69%) were men (median age 61). The prevalence of MAFLD was 55.3% at follow-up and 37.3% on admission ( P < .001). Insulin resistance (odds ratio [OR] = 1.5; 95% confidence interval [CI], 1.14–1.96), body mass index (OR = 1.14; 95% CI, 1.04–1.24), and the metabolic syndrome (OR = 2.54; 95% CI, 1.13–5.68) were independent predictors of MAFLD. The number of PACS clusters was inversely associated with MAFLD (OR = 0.86; 95% CI, .76–0.97). Thirty-one patients (13.2%) had MAFLD with no other associated PACS clusters. All correlations between MAFLD and other PACS clusters were weak. Conclusions: Metabolic-associated fatty liver disease was highly prevalent after hospital discharge and may represent a specific PACS-cluster phenotype, with potential long-term metabolic and cardiovascular health implications. Abstract : It has been proposed that Non-Alcoholic Fatty Liver Disease should be renamed Metabolic Associated Fatty Liver Disease (MAFLD) with potential long-term cardiovascular complications. MAFLD was highly prevalent after hospital discharge in COVID-19 and may represent a specific PACS-cluster phenotype.